2010
DOI: 10.1111/j.1365-3091.2009.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased terrigenous influx but no drowning: palaeoenvironmental evolution of the Tunisian carbonate platform margin during the Late Aptian

Abstract: During the Aptian, some carbonate platforms of the sub-tropical realm (for example, on the northern Tethys margin or in the Gulf of Mexico) were affected repeatedly by severe perturbations in the carbonate production factory and drowning, preferentially during global warming events such as the Early Aptian Oceanic Anoxic Event 1a and a prominent mid-Late Aptian warming interval. These platform growth crises have been explained mainly by strongly increased coastal runoff (for example, siliciclastics and nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…1B). Stratigraphic, sedimentologic and tectonic studies in this area have been undertaken since the beginning of the last century, and some of these studies have discussed the evolution of the sedimentary basins and the genesis of the ranges and associated structures (e.g., Pervinquière, 1903;Castany, 1954;Burollet, 1956;M'Rabet et al, 1979;Bismuth et al, 1981;Gargouri-Razgallah, 1983;Masse, 1984;Boltenhagen, 1985;Zargouni, 1985;Ouali et al, 1987;Abdallah 1989;Zouari et al, 1990Zouari et al, , 1999Boukadi, 1994;Negra, 1994;Abdallah et al, 1995Abdallah et al, , 2000Rabhi, 1999;Bédir et al, 2001; Bouaziz et al, 2002;Chaabani and Razgallah, 2006;Azaïez et al, 2007;Lazzez et al, 2008;Zouaghi, 2008;Gallala et al, 2009;Lehmann et al, 2009;Heldt et al, 2010). Other studies have shown that the Cretaceous strata in the central Atlas Mountains of Tunisia are organized into units and sequences (e.g., Tlatli, 1980;Bismuth et al, 1981;M'Rabet, 1981;Masse, 1984;Boltenhagen, 1985;Abdallah, 1989;Ben Youssef et al, 1989;Neri et al, 1991;Abdallah et al, 1995Abdallah et al, , 2000Chaabani, 1995;Sa...…”
Section: Geological Settingmentioning
confidence: 97%
See 1 more Smart Citation
“…1B). Stratigraphic, sedimentologic and tectonic studies in this area have been undertaken since the beginning of the last century, and some of these studies have discussed the evolution of the sedimentary basins and the genesis of the ranges and associated structures (e.g., Pervinquière, 1903;Castany, 1954;Burollet, 1956;M'Rabet et al, 1979;Bismuth et al, 1981;Gargouri-Razgallah, 1983;Masse, 1984;Boltenhagen, 1985;Zargouni, 1985;Ouali et al, 1987;Abdallah 1989;Zouari et al, 1990Zouari et al, , 1999Boukadi, 1994;Negra, 1994;Abdallah et al, 1995Abdallah et al, , 2000Rabhi, 1999;Bédir et al, 2001; Bouaziz et al, 2002;Chaabani and Razgallah, 2006;Azaïez et al, 2007;Lazzez et al, 2008;Zouaghi, 2008;Gallala et al, 2009;Lehmann et al, 2009;Heldt et al, 2010). Other studies have shown that the Cretaceous strata in the central Atlas Mountains of Tunisia are organized into units and sequences (e.g., Tlatli, 1980;Bismuth et al, 1981;M'Rabet, 1981;Masse, 1984;Boltenhagen, 1985;Abdallah, 1989;Ben Youssef et al, 1989;Neri et al, 1991;Abdallah et al, 1995Abdallah et al, , 2000Chaabani, 1995;Sa...…”
Section: Geological Settingmentioning
confidence: 97%
“…16) with some reef buildings (M'Rabet et al, 1979;Tlatli, 1980;M'Rabet, 1981;Masse, 1984;Marie et al, 1984;Heldt et al, 2010).…”
Section: Cretaceous (Aptian) Structuresmentioning
confidence: 98%
“…The "Orbitolina Level" therefore is one of the tie-points for the calibration of the upper Aptian biostratigraphy of central and southern Tethyan carbonate platforms (cf. Simmons et al, 2000;Bachmann and Hirsch, 2006;Chihaoui et al, 2010;Embry et al, 2010;Heldt et al, 2010;Vincent et al, 2010;Cherchi and Schroeder, 2012).…”
Section: The Age Of the "Orbitolina Level"mentioning
confidence: 99%
“…8) invites to link the "Orbitolina Level" with processes that affected the global carbon cycle during the lower Cretaceous (cf. Weissert and Lini, 1991;Takashima et al, 2007;Heldt et al, 2010). The "Orbitolina Level" of the middle Gargasian, in all likelihood, formed at the same time as part of the "Niveau Fallot" formed in a hemipelagic setting connected to the Tethyan Ocean, and probably to the Thalmann black shale event in California and a dark horizon on the Mazagan Plateau (DSDP Site 545; cf.…”
Section: Regional-to-global Significance Of the Isotope Recordmentioning
confidence: 99%
See 1 more Smart Citation